Pulmonary embolism during pregnancy: How to avoid computed tomographic pulmonary angiography? - Marcelina Makuch; Marcin Makuch (Kazimierz Wielki University, 2020)
Pregnancy and the postpartum period are well-established risk factors for venous thromboembolism (VTE). Computed tomographic pulmonary angiography (CTPA) remains the gold standard in the diagnosis of pulmonary embolism (PE), but exposure to teratogenic factors should be avoided in pregnant women. A few years ago the YEARS algorithm was developed, primarily to determine the need for CTPA.